The lawmaking of national parliaments: rethinking Europeanisation patterns - Yevgenyeva, A (2009)
National parliaments are frequently labelled as the ‘victims’ of European integration and the EU is accused of causing the erosion of parliamentary democracy. This thesis reviews these claims by examining the influence of the European Union on national parliaments in their lawmaking capacity. The Europeanisation of legislatures is analysed at the level of the transformation of their competence as domestic lawmakers and ‘European players’ (Europeanisation of competence) and at the level of institutional and procedural adaptation (institutional Europeanisation). In this way, the thesis addresses some of the major cleavages causing disagreement between the proponents and opponents of the disempowerment of national parliaments. It is argued that the EU brings not only restrictions, but also benefits to the legislative activities of national representative institutions; and, in fact, the strengthening or weakening pattern of Europeanisation largely depends on parliamentary capacity and willingness to adapt. The study not only assesses the pattern of EU influence on the national parliaments of its Member States, but also examines whether similar processes can be identified in non-Member States. The analysis regarding non-Member States looks beyond the examples that are typically assessed by Europeanisation studies (e.g. the EEA, the EFTA and the candidate countries) and instead focuses on the case of Ukraine. The latter represents the Eastern neighbours of the EU that lack creditable membership prospects and would therefore be expected to demonstrate a weaker (if any) impact of the EU on its parliament. By building the links between the processes of Europeanisation within the EU and ‘far beyond’ its borders, this thesis aims to prove that the ‘de-parliamentarisation vs. re-parliamentarisation’ discussion is of much wider geographical relevance than it might appear at first sight.